Designing Of The Ngalah Data Electric Car Frame Using The Finite Element Method - Rifky Zaidani; Mochamad Mas’ud (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
The development of fossil fuel transportation continues to increase massively every time, and this condition is terrible news for the environment worldwide because the impact of gas emissions produced from burning fossil fuels is quite damaging to the environment. For this reason, based on the problems above, every country, including Indonesia, needs to contribute to maintaining and caring for environmental conditions from the threat of damage caused by pollution from burning fossil fuels. One of the efforts made by the Indonesian government to overcome this is to develop electric vehicles in collaboration with KEMRISTEK through the Indonesian Electric Car Championship (KMLI) event, which involves universities in Indonesia. One of the main parts of an electric car is the frame or chassis; for this reason, the author tries to design the best Frame for an electric car. Other leading factors such as the value of Stress, Deformation, and Factor of Safety, the method researchers use in this study is the Finite Element Method. The results showed that the frame did not fail and could meet the safety standards that the author had set.